2015
DOI: 10.7205/milmed-d-14-00703
|View full text |Cite
|
Sign up to set email alerts
|

Age and Aortic Diameters in Pilots

Abstract: Jet pilots had aortic enlargement as they became older in contrast to the NJP group. Although the aortic diameters were not within the critical ranges in the JP group, these results could suggest that flight-related stresses might result in acute aortic syndromes in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…These findings were supported by a recent study that demonstrated that a significant MAP increase was associated with a progressive rise in the +Gz 2 . A more recent study 5 reported a significant AR and AA dilatation in jet aircraft pilots compared with non–jet aircraft pilots. Besides, this study supported a previous report, which demonstrated that repeated strenuous activity in military veterans is associated with dilated AR and AA 6…”
Section: Discussionsupporting
confidence: 71%
“…These findings were supported by a recent study that demonstrated that a significant MAP increase was associated with a progressive rise in the +Gz 2 . A more recent study 5 reported a significant AR and AA dilatation in jet aircraft pilots compared with non–jet aircraft pilots. Besides, this study supported a previous report, which demonstrated that repeated strenuous activity in military veterans is associated with dilated AR and AA 6…”
Section: Discussionsupporting
confidence: 71%
“…Harris et al found that non-Caucasian race was a risk factor for aortic dissection, similarly in this study, non-Caucasian race increased the risk for TAI [22]. Other studies have also shown associations between various sports activities and development of TAI [7][8][9][10][11]. In this study the cause of injury was a significant confounder for the association between TAI and altitude, among the patients with a TAI only those at high altitudes had sports injuries as the cause of injury.…”
Section: Discussionsupporting
confidence: 80%
“…Schachner et al identified skiers at an increased risk for aortic injuries, which may be related to the fact that skiers are often performing at high altitudes [11]. Other studies have identified activities thought to increase the risk for TAI including professional sports, weight lifting, and military training [7][8][9]. One case study reported a TAI after a paragliding accident [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations